A combined Raman optical activity and vibrational circular dichroism study on artemisinin-type products. Issue 32 (5th August 2020) - Bogaerts, Jonathan; Desmet, Filip; Aerts, Roy; Bultinck, Patrick; Herrebout, Wouter; Johannessen, Christian
Abstract : Artemisinin and two of its derivatives, dihydroartemisinin and artesunate, front line drugs against malaria, were studied using Raman optical activity (ROA), vibrational circular dichroism (VCD) experiments and density functional theory (DFT) calculations. Abstract : Artemisinin and two of its derivatives, dihydroartemisinin and artesunate, which are front line drugs against malaria, were investigated using Raman optical activity (ROA) and vibrational circular dichroism (VCD) experiments, both supported by density functional theory (DFT) level calculations. The experimental techniques combined with DFT calculations could show that dihydroartemisinin was present as an epimeric mixture in solution. In addition, an approximation of the epimeric ratio could be extracted which was in agreement with the ratio obtained by 1 H-NMR spectroscopy. The current study also demonstrates that both ROA and VCD are able to assign the correct absolute configuration (AC) of artemisinin and artesunate out of all their possible diastereomers without any explicit knowledge on their correct stereochemistry and accentuates the synergetic effect between ROA and VCD in AC determination.